2022
DOI: 10.3390/ijerph19052502
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Power of Clean Rivers: In Silico Evaluation of the Antipsoriatic Potential of Apiin and Hyperoside Plant Metabolites Contained in River Waters

Abstract: Humanity may benefit greatly from intact riverine ecosystems not only because they supply water to be used in the most common human activities, but also for the effects that clean rivers can have on human health. Herein, we used a computational approach to show that some phytochemicals produced by riparian plants as secondary metabolites, which are naturally released into river waters, can have therapeutic properties. These include antipsoriatic activities which we demonstrated in silico by modelling the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It is perhaps our long connection with nature which makes forests ideal locations to de-stress but these benefits are not limited to woodlands. It has been found that humans also benefit enormously from the positive effects of spending time near clean rivers [101,102]. Good quality river water together with thriving biodiversity and a healthy riparian habitat structure combine to create a beneficial space for people to enjoy exercise or sessions of relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…It is perhaps our long connection with nature which makes forests ideal locations to de-stress but these benefits are not limited to woodlands. It has been found that humans also benefit enormously from the positive effects of spending time near clean rivers [101,102]. Good quality river water together with thriving biodiversity and a healthy riparian habitat structure combine to create a beneficial space for people to enjoy exercise or sessions of relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking (MD) simulations [ 7 , 64 , 65 , 66 , 67 , 68 ] were performed running the HDOCK server ( , accessed on 30 May 2022) [ 69 , 70 ], suitable for both macromolecule-to-macromolecule [ 69 ] and macromolecules-to-small molecules [ 71 ] rigid dockings, using default parameters. The PDB entry 4f5s [ 72 ] and the energy-minimized 3D structure models of U2O and T2O (obtained by MOLVIEW ( , accessed on 30 May 2022), and saved as .pdb files) were uploaded into the HDOCK server as the target and ligands, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A protective effect on human populations by evergreen forests against pandemics was suggested recently due to trees not only reducing air pollution by collecting PM onto plant surfaces but also due to their ability to strengthen the human immune system by generating bioactive volatile organic compounds (VOCs) that when inhaled stimulate the body's defenses [12,13]. This supports the development of 'forest bathing' [14,15] as a therapeutic technique, the creation of nasal sprays containing the most bioactive plant VOCs, the preservation of ecosystems, and most importantly, initiatives promoting an expansion of the areas covered by forests worldwide [16,17].…”
Section: Introductionmentioning
confidence: 98%